Putting teens first in library services : a road map - Braun, Linda W.; Peterson, Shannon (Young Adult Library Services Association (YALSA), a division of the American Library Association (ALA), 2017)
In this collection of essays, staff working directly with teens explore ideas, services and programs that continue to evolve within their libraries. The challenges revealed emphasize the fact that neglecting teen library services risks a future in which libraries themselves are no longer valuable to the community and the potential advocates which todays teenagers will someday become.